THE ART OF ENGLISH USAGES – LESSONS LEARNT FROM A TEACHER DEVELOPMENT FIELD TRIP - Tan, Nguyen Thi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Field trip is one of the most indispensable ways of learning which has been widely recommend by research scholars, learning English in real life contexts is not a rarity to maximize learners’ language capability and universal understanding. However, several groups of Vietnamese English students may not have fully validated the knowledge fact about the key role of English learning recently. This narrative qualitative study conducted by an English teacher is to reveal the tangible benefits of English learning through a teacher development field trip in England, the United Kingdom for students’ personal education goals and teachers’ professional development aspirations.